Intravitreal Dexamethasone Implant in the Treatment of Non-infectious Uveitis - Murat Hasanreisoğlu; Hüseyin Baran Özdemir; Kaan Özkan; Murat Yüksel; Zeynep Aktaş; Hatice Tuba Atalay; Şengül Özdek; Gökhan Gürelik (Türk Oftalmoloji Dergisi, 2019)

(untitled)
Objectives:To evaluate the long-term results of intravitreal dexamethasone implant (DEX) for noninfectious uveitis.Materials and Methods:The study included 62 eyes of 44 patients treated with DEX implant due to noninfectious uveitis and followed up for at least a year. Best-corrected visual acuity (BCVA), central foveal thickness, intraocular pressure (IOP), vitreous haze score, indications, immunomodulatory therapy and steroid usage before/after injection, number of injections, and adverse events were analyzed retrospectively.Results:Average follow-up was 20 months (range 12-64 months). The female/male ratio was 29/15. Mean age was 50 years (range 22-75 years). The most frequent uveitis etiologies were idiopathic (25 patients, 40.3%) and Behçet’s uveitis. (17 patients, 27.4%) The signedmost common indication for DEX injection was cystoid macular edema together with resistant vitreous haze (26 eyes, 41.9%). Twenty-two eyes (30%) received more than one DEX injection. Mean BCVA was improved from 0.55 logMAR at baseline to 0.38, 0.32, and 0.35 after 1, 3, and 6 months, respectively (p<0.001 for each). Mean CFT was decreased from 386 μm at baseline to 288, 311, and 302 μm after 1, 3, and 6 months, respectively (p<0.001 for each). Mean IOP did not change significantly during follow-up. Five eyes (8%) received topical anti-glaucoma medication (IOP ≥25 mmHg). Eighteen (46%) of 39 phakic eyes underwent cataract surgery during follow-up. Similar efficacy of the DEX implant was observed in eyes that received multiple injections. Systemic immunomodulatory therapy did not change significantly during follow-up.Conclusion:Intravitreal DEX injection does not alter systemic immunomodulatory therapy, but may facilitate the management of noninfectious uveitis by suppressing local intraocular inflammation. Multiple injections yielded comparable visual and anatomical outcomes to single injections. Follow-up for ocular hypertension and cataract formation are important, especially in eyes receiving multiple injections.